2022
DOI: 10.3390/jfb13020062
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Osteogenic Properties of Ag Nanoparticles and Ag/TiO2 Nanostructures Prepared by Atomic Layer Deposition

Abstract: The combination of titania nanofilms and silver nanoparticles (NPs) is a very promising material, with antibacterial and osseointegration-induced properties for titanium implant coatings. In this work, we successfully prepared TiO2 nanolayer/Ag NP structures on titanium disks using atomic layer deposition (ALD). The samples were studied by scanning electron microscopy (SEM), X-ray diffraction, X-ray photoelectron spectroscopy (XPS), contact angle measurements, and SEM-EDS. Antibacterial activity was tested aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…To simulate peri-operative infection, in the co-culture experiment, bacteria were permitted to adhere for 2 h before cell adhesion. In co-culture experiments, cells are planned to be stained for different periods (3,6,12, and 24 h). However, it was found that after the co-culture of bacteria and cells for more than 6 h, cells began to damage or even die.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To simulate peri-operative infection, in the co-culture experiment, bacteria were permitted to adhere for 2 h before cell adhesion. In co-culture experiments, cells are planned to be stained for different periods (3,6,12, and 24 h). However, it was found that after the co-culture of bacteria and cells for more than 6 h, cells began to damage or even die.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1 mL of prepared S. aureus suspension (1 × 10 6 CFU/mL) was added into the 24-well plate containing Ti and Ta plates and cultured for different periods (3,6,12, and 24 h) at 37 • C. At each time point, the spread plate method was used to calculate the number of planktonic bacteria and to analyze the bacteria adhered to the surface of the samples using SEM after ultrasonic vibration [43].…”
Section: In Vitro Antibacterial Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…AgNPs were deposited by the ALD method on a Picosun R-150 setup using the Ag (fod) (PEt 3 ) precursor and hydrogen plasma as a reducing agent, as described in Ref. [45]. To determine the optimal growth condition, the reactor temperatures (142-184 • C), (Ag (fod) (PEt 3 )) container temperatures (115-150 • C), reagents pulse times (2-4 s) and number of pulses (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) in one ALD cycle were varied.…”
Section: Precipitation Of Agnps By Ald Methodsmentioning
confidence: 99%